ENGLISH STUDENTS’ PERCEPTION OF USING CHATGPT IN ACADEMIC VOCABULARY SUBJECT - Yulia Kurniadi; Yendra Yendra; Willy Satria (Universitas PGRI Sumatera Barat, 2025)
This study aims to examine students’ perceptions of using ChatGPT in learning academic vocabulary. The research was conducted among English Education students at Universitas PGRI Sumatera Barat, class of 2024, who have used ChatGPT in the Academic Vocabulary course. This study employed a descriptive qualitative approach with data collected through semi-structured interviews with 4 students who were selected purposively. The data were analyzed using thematic analysis based on four indicators: emotions, past experiences, personal values, and social influences. The findings indicate that the majority of students hold positive perceptions toward ChatGPT, as it is considered to facilitate material comprehension, enhance learning motivation, and boost self-confidence. However, some respondents also expressed concerns regarding potential dependency and the limitations of the language style used by ChatGPT. These findings suggest that ChatGPT can serve as an effective learning medium in supporting academic vocabulary acquisition, provided it is used critically and in a balanced manner. This research offers new insights into the integration of AI in language learning and serves as a foundation for developing more adaptive and reflective technology-based learning strategies.